Scaling Profitability: A Business Development Strategy for LCD Display Machines in the Air Compressor Industry - Fadhillah, Ahmad; Dora, Yenny Maya (Yayasan Riset dan Pengembangan Intelektual, 2024)
Screw-type air compressors are essential in modern industries, supporting various manufacturing operations such as textile, automotive, energy, and healthcare. However, operational issues like overcooling and overheating frequently hinder efficiency due to inadequate user understanding and lack of after-sales support. This business plan aims to address these challenges by integrating innovative LCD displays for screw compressors, enhancing operational monitoring and maintenance scheduling. Utilizing a design thinking approach and Business Model Canvas framework, the study employs both qualitative and quantitative methods to analyze market needs and technological feasibility. Findings reveal that the integration of Planned and Unplanned Maintenance features into the LCD display significantly improves machine reliability and user accessibility. This innovation supports cost-efficient operations and provides competitive advantages for PT. Guna Mitra Sinergi. The implications underline the necessity for local suppliers to invest in advanced solutions to maintain market competitiveness and ensure sustainability.